5-Axis tool path planning based on highly parallel discrete volumetric geometry representation: Part I contact point generation. Issue 1 (2nd January 2018) - Konobrytskyi, Dmytro; Hossain, Mohammad M.; Tucker, Thomas M.; Tarbutton, Joshua A.; Kurfess, Thomas R.
ABSTRACT: While 5-axis CNC machines improve the manufacturing productivity, the tool-path programming demands human expertise and tremendous time investment to generate collision-free optimal tool trajectories. To address the challenge of multi-axis CNC programming, this work presents a new discrete volume based geometry representation that naturally enables highly parallel geometry processing. Then it formulates and discusses a methodology for tool path planning algorithms designed around the formulated geometric representation for 5-axis CNC milling machines and ball end tools. This paper is the first of two papers that deals with finding the XYZ locations of ball end mill centers that govern the tool trajectories. The experimental 5-axis machining using the resulting tool paths demonstrates that the designed algorithms are capable of producing collision- and gouge- free tool paths with a desired surface quality for a given target geometry by using the selected ball end tools. GRAPHICAL ABSTRACT: